ANALISIS PENGENDALIAN KUALITAS UNTUK MENGURANGI DEFECT PADA PRODUK BENCH LEG (STUDI KASUS DI PT XYZ) - MUHAMMAD HAGI FAHREZI; Herlina K Nurtjahyo; Gayuh Lemadi (Fakultas Sains Dan Teknologi, 2024)
PT XYZ is a manufacturing company engaged in the musical instrument manufacturing industry, such as: pianos, etc. One of the supporting components produced by PT XYZ is the bench leg product (legs on a piano bench) where many defective products were still found in January 2024 to March 2024. There were types of deck defects with a total of 1493 defects, 557 bubble defects. pcs, cutter mark defects were 332 pcs, and grooves were 172. Therefore, this research aims to determine the main causes of defects and provide suggestions for improvements to minimize the occurrence of defects. This can be done by carrying out quality control using the seven tools method and Failure Mode and Effect Analysis (FMEA). Data collection techniques use observation, interviews and documentation techniques. The results of this research after data processing and analysis showed that in the Pareto diagram the highest defect was found, namely decoction with a percentage of 60% and became the focus of improvement, and in the P-Chart analysis it was found that the bench leg line production process was still not controlled. After being identified using a fishbone chart, 16 potential causes of deck defects were obtained, followed by FMEA analysis, the results of the Pareto diagram from FMEA showed the largest RPN value with a score of 432, namely FM 4 (Placement of finished good products using shelves and products stacked on top of other products). By finding the root of the problem, a suggestion for improvement that can be made is to replace the shelf for placing the finished good product using a box that is equipped with felt on the surface of the box and sides of the box to minimize collisions, and there is no accumulation of product on top of the product. Keywords: dekok defect, Bench Leg, FMEA, Seven Tools